Maltreatment experiences and psychopathology in children and adolescents: the intervening role of domain-specific self-representations moderated by age - Silva, C. S.; Calheiros, M. M. (Child Abuse and Neglect, 2020)
Background: Associations between maltreatment experiences and psychopathology symptoms in children and adolescents are well established. However, the role of domain-specific self-representations (SR) in those associations remains unexplored. Objective: This multi-informant study aimed to explore the indirect associations between maltreatment experiences and children's and adolescents’ psychopathology symptoms (i.e., internalizing and externalizing problems), through domain-specific self-representations, and the moderating role of age in those indirect associations. Participants and setting: Participants were 203 children/adolescents (52.7 % boys), aged 8–16 years old (M = 12.64; SD = 2.47), referred to child/youth protection commissions, their parents, and case workers. Method: Case workers reported on child/adolescent maltreatment, children/adolescents reported on SR, and parents reported on psychopathology symptoms. Results: Controlling for chronicity of maltreatment and child/adolescent sex effects, multiple mediation path analysis revealed that: 1) higher levels of physical and psychological abuse were associated with less externalizing problems through more negative social SR; 2) higher levels of physical neglect were associated with more externalizing problems through more positive opposition SR; 3) higher levels of psychological neglect were associated with less externalizing problems through more negative physical appearance SR, and 4) associated with more externalizing problems through more negative opposition SR. Moreover, the indirect effects of physical and psychological abuse on internalizing and externalizing problems through instrumental SR were conditional on child/adolescent age. Conclusion: Findings signal the relevance of preventing child/adolescent maltreatment and promoting the construction of positive and, foremost, realistic and adaptive self-representations as protection against maladjustment.